Incidence rate of hemorrhagic fever with renal syndrome complicated with acute pancreatitis: a meta-analysis - Ye, Zhenzhen; Liu, Xiaoqing; Ding, Sheng; Lu, Ling; Zhang, Tianchen; Zhou, Wenfang; Dong, Yonghai (Frontiers in Medicine, 2024)
Background: Acute pancreatitis (AP) is a rare but serious complication in patients diagnosed with hemorrhagic fever with renal syndrome (HFRS). When AP complicates HFRS, the clinical outcome significantly worsens and the risk of mortality increases. However, the incidence of AP in HFRS patients and its associated mortality risk remain unclear. To address this knowledge gap, we conducted a meta-analysis to determine the AP incidence rate in HFRS patients and assess the impact of AP on mortality in these patients.: We systematically searched seven databases (PubMed, Web of Science, EMBase, Sinomed, Chinese National Knowledge Infrastructure, WanFang Data, and Chongqing VIP) for relevant studies on HFRS complicated by AP. The studies were selected using predefined inclusion and exclusion criteria based on the Population, Intervention, Comparison, Outcome, and Study design principle. Two independent reviewers screened the studies, and the quality of the included studies was assessed using the Agency for Healthcare Research and Quality and the Newcastle-Ottawa Evaluation Scale (NOS).Results: In total, 11 studies, encompassing 1,218 HFRS patients, met the inclusion criteria. The overall incidence of HFRS complicated by AP was 8.5% (95% CI for r 5.9%-11.1%). The HFRS patients with AP had a significantly higher risk of mortality than those without AP (OR = 3.668, 95% CI for OR 1.112-12.031). No statistically significant differences were observed in the subgroup and meta-regression analyses.Although the incidence of AP in HFRS patients is not high, it significantly increases the risk of mortality in these patients. Future large-scale prospective studies are required to further validate these findings.